The Influence of the Mother Tongue on English Pronunciation: A Case Study on Indonesian EFL Learners - Listyani; Kurniawan, Ardiyarso; Thren, Andrew T. (JET (Journal of English Teaching), 2024)
Pronunciation is an area of language, which is easy to recognize and see. When a language learner makes an error in pronunciation, other people can identify the error easily. Mispronunciations are common errors that happen to English language learners in the Expanding Circle, in which English is a foreign language, like Indonesia. This paper deals with mispronunciations made by Indonesian language learners. The respondents were 14 students of a writing class in an English Language Education Program at a private university in Indonesia. They took the course during the pandemic era. The classes were therefore done online, and each virtual class was recorded. These students were video-recorded when reading certain parts of texts in the course. The findings showed that the 14 students made some mispronunciations due to several reasons like habits of pronouncing words in Indonesian and a lack of knowledge of the ideal notion of native speakers' pronunciation. It is hoped that this paper can be useful for EFL teachers teaching pronunciation as well as for students who are still struggling with their pronunciation in their efforts to gain native-like proficiency.